Looking into e-learning in Bangladesh implementing SUDOKU puzzle and KUMON learning system - Mishu, Sheikh Mohammad Ashrafullah; Khairullah, Rahat; Roy, Sumit (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007